A prosódia da expressividade facial das emoções de crianças com síndrome de down do município de Abaetetuba - ALMEIDA, Rosane Rodrigues de (2019)
In this study we understood, especially, the prosodic processing of facial expressions of children with Down Syndrome. We assumed that children with Down Syndrome would have barriers to understand and produce the emotional facial expressions due to restricted social interactions. We have adopted as theoretical bases the thoughts of Fónagy (2003) and Paul Ekman cited by Correia (2014). According to Fónagy (2003), the prosody can express the attitude, the emotion and/or the intention of its collocutor. Paul Ekman (1999) cited by Correia (2014) defines six basic emotions: happiness, sadness, anger, fear, disgust and surprise. Were participant to this study 6 children, being 3 with and 3 without Down Syndrome. The material composed six primary facial expressions of basic emotions, based on Paul Ekman, as known: happiness, sadness, anger, fear, disgust and surprise. The task consisted in two phases: the first one we asked the children with and without Down Syndrome to produce the six facial expressions by spontaneous narratives. Posteriorly they were induced to recognize the six basic facial expressions cited above by looking to 6 figures taken from the internet. By all means, the results showed that participants with Down Syndrome understood 6 (six) emotions, being only one able to recognize all of them, the other two participants have recognized just the prosodic reactions of happiness, fear and sadness. And all three of them were capable of producing 5 (five) emotions, being: happiness, sadness, surprise, fear and anger. Although the participants without Down Syndrome were able to understand 5 (five) emotions: happiness, sadness, anger, disgust and surprise. And were capable of producing 6 (six) emotions: happiness, sadness, anger, fear, disgust and surprise. These evidences confirm our hypothesis that the children with Down Syndrome would show barriers to understand and produce the emotional facial expressions due to restricted social interactions.